THE CORRELATION BETWEEN DIGITAL LITERACY AND ENGLISH PROFICIENCY OF UNIKA MUSI CHARITAS FIRST-YEAR STUDENTS - Anastasia Ronauli Hasibuan; Ira Irzawati (Didascein : Journal of English Education, 2020)
This study aimed to discover the correlation between digital literacy and English proficiency of first-year students at Unika Musi Charitas. One hundred seventy three students were involved by using purposive sampling technique. The data were collected by using questionnaire which elaborates students’ digital literacy as well as the score of their English proficiency. To analyze the results, Pearson Product Moment formula was used to measure the relationship between the two discussed variables. Findings were described into the results of participants’ English proficiency level, digital literacy insight as well as the correlation test. Viewing from the proficiency level, 64.2% of the participants were categorized as basic users which can perform limited language use on daily topics. In addition, the mean score of their digital literacy insight was 66.99 with the maximum and minimum scores were 100 and 10 descriptively. The correlation test obtained significant correlation between digital literacy and English proficiency with Pearson correlation value of 0.394 at significance level of 0.000. This strongly confirms that the ability of using digital things and language carry positive intercourse.Keywords: Digital literacy, English proficiency